Cleaner production of methyl ester using waste cooking oil derived from palm olein using a hydrodynamic cavitation reactor - Chuah, L.F. (Elsevier Ltd, 2016)
Methyl ester contributes to environmental protection as it is biodegradable, renewable, non-toxic, produces less sulphur oxides emissions and greenhouse gases. The present work highlights the potential of hydrodynamic cavitation for the methyl ester production from waste cooking oil. The transesterification process was conducted under optimised conditions, such as oil to methanol molar ratio of 1:6 in the presence of 1 wt. potassium hydroxide as alkali catalyst at 60 Â°C. Four newly designed orifice plate geometries induced cavities assisted by a double diaphragm pump in a pilot hydrodynamic cavitation reactor were investigated. It is shown that the high turbulence generated by the cavitating bubbles were effective in reducing the mass transfer resistance between immiscible reactants during the transesterification reaction due to increased interfacial area. At 2 bar inlet pressure, orifice plate with 21 holes of 1 mm diameter resulted in 8 fold higher yield efficiency and 6 fold lower reaction time compared to mechanical stirring. This makes the process more environmental friendly by using hydrodynamic cavitation. In conclusion, waste cooking oil methyl ester produced via hydrodynamic cavitation proved to be energy efficiency and time saving. The properties of the produced methyl ester met both EN 14214 and ASTM D 6751 standards. Â© 2015 Elsevier Ltd. All rights reserved.